Characteristics of Erectile Dysfunction Patients in the Andrology Unit of Dr. Soetomo Hospital, Surabaya, Indonesia - Akmal Ramadhan (Journal of Global Pharma Technology, 2016)
Erectile dysfunction (ED) is a common problem in the medical field. In contrast to worldwide data, the prevalence of ED and its risk facftors in Indonesia is still unknown. The objective of this study was to determined the characteristics of male erectile dysfunction patients in the andrology unit of Dr. Soetomo hospital, Surabaya, Indonesia. A descriptive cross-sectional design was implemented in this study. There were 83 male patients at URJ Andrology RSUD dr. Soetomo Surabaya. The highest prevalence of erectile dysfunction patients in the age group was age 41-50 years old (22.9%). The degree of IIEF-5 was the most in severe degree (39.8%), while the EHS score was the most in score 2 (38.6%). The highest internal risk factors were vasculogenic (90.4%), the external risk factors was the lifesyle factor (56.6%). In Surabaya, Indonesia, the incidence of erectile dysfunction has increased in the 40 year age group with severe degree, which mostly caused by vascular disorder combined with lifestyle factors. Multidisciplinary treatment and healthy life are needed for erectile dysfunction management to improve the quality of life.Keywords: Erectile dysfunction, Patient characteristic, Surabaya, Indonesia.